COVID-19 and Global Value Chains: Trigger for a Sound Economic Order? - Florian Butollo (WZB Berlin Social Science Center, 2020)
Can coronavirus trigger a sound economic order? Scepticism is advisable.
Keywords: 300; contagious disease; Coronavirus; COVID-19; epidemic; globalization; international economic relations; value chain